The influence of grazing load of different intensity on the state of zoo-microbial complex in the soils of Tuva dry steppes - Yakutin Mikhail V.; Andrievskii Vladislav S. (BIO Web of Conferences)
The paper presents the results of a study of the features of the transformation of various components of the zoo-microbial complex during long-term use of the steppe ecosystem as a pasture under a strong load compared to pasture areas under a weak load. It was revealed that various components of the zoo-microbial complex are characterized by fundamentally different reactions to such a widespread anthropogenic factor in the steppe zone as grazing load. It was determined that when the constant grazing load changes from weak to strong, a reliable increase in the C-biomass of microorganisms occurs. It was found that areas of dry steppe that have been under a weak grazing load for a long time are characterized by significantly higher quantitative indicators of oribatid mite communities, such as species richness and total abundance, compared to an area of the dry steppe ecosystem that has been under a strong grazing load for a long time. As a result of the conducted acarological analysis, the statement is substantiated that under a weak but stable load, the oribatid communities have a moderately high number, while under a strong grazing load, the oribatid community is in a depressed state. The conclusion is presented that the indicators of soil microbial biomass, number and species richness of oribatid mites can be successfully used in the practice of environmental monitoring of steppe ecosystems under varying grazing loads.